2018
DOI: 10.1111/ejn.13838
|View full text |Cite
|
Sign up to set email alerts
|

Dance on cortex: enhanced theta synchrony in experts when watching a dance piece

Abstract: When watching performing arts, a wide and complex network of brain processes emerge. These processes can be shaped by professional expertise. When compared to laymen, dancers have enhanced processes in observation of short dance movement and listening to music. But how do the cortical processes differ in musicians and dancers when watching an audio-visual dance performance? In our study, we presented the participants long excerpts from the contemporary dance choreography of Carmen. During multimodal movement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 77 publications
2
25
0
2
Order By: Relevance
“…This effect may be attributed to plasticity changes occurring after intense body training (Giacosa et al, 2016;Hänggi et al, 2010), as in the case of increased grey matter (GM) volume found in the posterior hippocampal formation and in the lingual /fusiform gyri in dancers (Hüfner et al, 2011). These findings would strengthen the assumption of a more efficient visuomotor network in experts when compared with non-experts (Babiloni et al, 2010;Nakata et al, 2010;Pau et al, 2013;Poikonen et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…This effect may be attributed to plasticity changes occurring after intense body training (Giacosa et al, 2016;Hänggi et al, 2010), as in the case of increased grey matter (GM) volume found in the posterior hippocampal formation and in the lingual /fusiform gyri in dancers (Hüfner et al, 2011). These findings would strengthen the assumption of a more efficient visuomotor network in experts when compared with non-experts (Babiloni et al, 2010;Nakata et al, 2010;Pau et al, 2013;Poikonen et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…For the participants who like dancing, music is comprehensive and collaborative. Music forms a setting in which dancers produce movements that are coherent with (or intentionally in contrast to) the prevailing sound in terms of rhythm, sentiment, and movement style (Poikonen et al 2018a). When freely listening, a participant might be more focused on the gist of the music than to the sequence of an individual instrument, melody contour, or rhythmic pattern.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the experiment, a 90-seconds resting EEG was collected with the participant’s eyes open and a 90-second resting EEG with eyes closed. The resting-state EEG was collected to compare resting EEG between the groups, reported in [ 15 ]. This is a crucial control condition if significant changes occur between groups during tasks.…”
Section: Methodsmentioning
confidence: 99%
“…While functional MRI (fMRI) studies highlight the importance of premotor areas in professional dancers when watching dance [ 8 ], musicians have refined function on regions related to memory and auditory-motor integration when listening to music [ 7 , 13 ]. In our two previous studies, we showed that dancers and musicians process fast changes in continuous music differently [ 14 ] and that the synchrony of activation is stronger in dancers than in musicians and laymen when watching an audiovisual dance piece [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation